Complications of Diabetes: Chronic Kidney Disease (CKD) and Diabetic Nephropathy - Büyükbeşe, Mehmet Akif (JOP. Journal of the Pancreas, 2014)
Today, almost half of the patients who are on chronic kidney replacement therapy have diabetes. The enormous worldwide rise in these cases pose potential economic burden for every country and therefore monitoring kidney function should be a practice provided in outpatient settings. Poorly controlled diabetes will not only result in chronic renal failure, but also patients with chronic renal disease will have some metabolic abnormalities that will increase both morbidity and mortality of the patients. While hypertension may associate with most of the diabetic cases, those people with diabetes who have no rise in blood pressure will eventually develop hypertension at later stage of the chronic kidney disease. Many inflammation markers present in case of diabetes, may contribute somehow further to the deterioration of the kidney function especially in those who do not have a properly controlled glucose excursions during day and night. Increased serum creatinine level is considered a definite marker of very late stage chronic renal failure that should be kept in mind. In order to avert increasing the rate of waiting list for kidney transplantation, monitorizing the level of microalbuminuria should be a routine practice delivered in general practitioner’s offices.